Cellulose acetate/poly(vinyl alcohol) hybrid fibrous mat containing tetracycline hydrochloride and phenytoin sodium: Morphology, drug release, antibacterial, and cell culture studies. (November 2018) - Souriyan-Reyhani pour, Hamed; Khajavi, Ramin; Yazdanshenas, Mohammad Esmaeil; Zahedi, Payam; Mirjalili, Mohammad
The objective of this study was to introduce an electrospun hybrid fibrous mat (a dual-fiber drug delivery system) based on cellulose acetate and poly(vinyl alcohol) containing tetracycline hydrochloride and phenytoin sodium, respectively. Characterization of samples was carried by morphology, drug release, cell cytotoxicity, adhesion, antibacterial property, and wettability investigations. The results showed a uniform shape and a narrow diameter distribution of fibers (between 160 ± 20 nm) for fabricated cellulose acetate/poly(vinyl alcohol) hybrid fibrous mat. The tetracycline hydrochloride release from cellulose acetate significantly decreased due to gel formation of poly(vinyl alcohol) in aqueous media. The best fit for drug release kinetic of hybrid sample was Higuchi model. Sample with tetracycline hydrochloride and phenytoin sodium drugs showed improved cell growth, viability, and antibacterial activity against Escherichia coli ( 89%) and Staphylococcus aureus ( 98%) in comparison with sample without drugs. The hydrophilic property of cellulose acetate/poly(vinyl alcohol) fibrous sample containing the drugs was also remarkable ( 45°). To consider the obtained results, the presented hybrid fibrous mat shows a high potent for biomedical applications.